Computing and optimization for DC power systems of electric transport - Bosyi, Dmytro; Sablin, Oleh; Kosariev, Yevhen (New Jersey : World Scientific, 2020)
'In the modern world, further development of society is impossible without environmentally friendly modes of transport and their effective interaction within the framework of Smart Energy and ECO-driving concepts. Written at a time of rapid development of information technologies in various fields, this book serves as a kind of bridge for the introduction of artificial intelligence into the electric transport power supply systems. The calculation models and methods proposed make it possible to choose the most efficient modern equipment for electric power supply of electric vehicles, which, as a result, saves investment costs and reduces time to make decisions designing complex objects. Insight is also given into building and adjusting Smart Energy class equipment to achieve optimal and economical modes'--
Includes bibliographical references and index.
Keywords: Electric railroads -- Power supply; Electric power systems -- Control -- Data processing; Electric power transmission -- Direct current